Acceptance of the initiative on second homes - Christophe Clivaz (Revue de Géographie Alpine)
The acceptance of the initiative to limit second homes was a real shock for Swiss tourist regions. By placing this decision in the more general context of the debate on the advantages and disadvantages of a resort development model based on the construction of second homes, we first review the role of the Swiss public authorities in managing this issue, a role that until now has been somewhat limited. We also draw attention to the discrepancy between the rhetoric of politicians and tourism officials, who are in favour of a restriction on building new second homes, and the reality on the ground, where the construction of new second homes continues unabated. Our main hypothesis is that the modification of the legal framework imposed by the acceptance of the initiative will compel tourism actors to innovate in order to put in place a new development model based on market accommodation, in other words to move from a “tourism of construction” to a “tourism of services”.